1979
DOI: 10.1113/jphysiol.1979.sp012698
|View full text |Cite
|
Sign up to set email alerts
|

Free‐flow reabsorption of glucose, sodium, osmoles and water in rat proximal convoluted tubule.

Abstract: 1. Reabsorption of glucose, sodium, total solute (osmoles) and water in the rat proximal tubule (pars convoluta) were studied by free‐flow micropuncture at normal (saline‐infused), suppressed (saline with phlorizin) and elevated (glucose infusion) glucose reabsorption rates. 2. Phlorizin completely inhibited net glucose reabsorption, approximately halved reabsorption of sodium, total solutes and water, and reduced single nephron glomerular filtration rate (SNGFR). 3. In saline and glucose‐infused groups, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…Indeed one study showed a tight coupling of the sodium-potassium ATPase to glycolysis in rat cardiomyocytes [77]. We also observed a higher fractional excretion of glucose after hypoxia compared to ischemia, which indicates that the hypoxic stress also interfered with the proximal tubule function [78]. All these factors may explain the worse outcome of renal function during hypoxia compared to the ischemic state.…”
Section: Glucosesupporting
confidence: 56%
“…Indeed one study showed a tight coupling of the sodium-potassium ATPase to glycolysis in rat cardiomyocytes [77]. We also observed a higher fractional excretion of glucose after hypoxia compared to ischemia, which indicates that the hypoxic stress also interfered with the proximal tubule function [78]. All these factors may explain the worse outcome of renal function during hypoxia compared to the ischemic state.…”
Section: Glucosesupporting
confidence: 56%